Preparation of zinc doped-biphasic calcium phosphate/carbon nanotube composites - -, Gunawan; Sopyan, Iis; Mel, Maizirwan; -, Suryanto (AENSI Publications, 2014)
Biphasic calcium phosphate (BCP) has been used in tissue engineering and orthopedics due to its good biocompatibility and osteoconductivity. However, its clinical applications are usually limited by the low strength and brittleness. The objective of this research was to develop Zn-doped BCP composites in which multi-wall carbon nanotubes (MWCNT) were introduced to the Zn-doped BCP ceramic matrix to improve the mechanical properties of the resulting composites. The starting powders have been synthesized via sol-gel method. Zinc concentration was varied in the range of 0, 1, 2, 4, 5, and 10mol%. After uniaxial pressing the compacted samples were sintered via conventional pressureless sintering. The samples were studied in terms of the phase stability, relative density, Vickers hardness, and fracture toughness as well as in vitro analysis in SBF solution. The results showed that hydroxyapatite as the main phase and β-tricalcium phosphate as the secondary phase of obtained powders. The morphology of the powders show the formation of nanocrystalline powder and individual particles are globular in shape.The maximum micro Vickers hardness and fracture toughness was achieved when fired at 1200oC, with 4.30 GPa and 2.0 MPa.m1/2, respectively. In vitro analysis shows that the samples have been covered by apatite cell since day one, and the density of apatite increased with immersion time in SBF. This study showed that CNT reinforcing was beneficial in producing high toughness of BCP without offsetting its bioactivity properties.